Oral health attitude and behaviour among dental students - Hariyani, Ninuk; Alghazaly, Farouk; Rahmi, Annafsa Zaky; Qaid, Huda Rashad; Ahmed, Suha Mudhish Abduljalil; Silitonga, Friska Miani; Bayasyut, Muhammad Fahmi; Shanbhag, Namita (Majalah Kedokteran Gigi Indonesia, 2024)
Dental students will play an important role in educating and promoting oral health. The oral health behavior of dental providers and their attitudes toward their oral health could depict the oral health of their patients. The aim of this study was to review the current studies available on the oral health attitudes and behavior of dental students. A systematic search of original articles was carried out in two databases to write this systematic review. MEDLINE (pubMed) and GOOGLE SCHOLAR. Studies published in the English, Arabic and Indonesian languages up to 31/6/2023 was carried out. Search results were managed through EndNote. The search strategy identified 180 articles (133 from Google Scholar and 47 from PubMed databases), of which 22 articles were included in the analysis after the systematic review process. Study of oral health attitude and behavior based on the Hiroshima University Dental Behavioral Inventory (HU-DBI). As a result of variation in the subjects age, measure of outcomes quantitative analysis is not showed. A total of 22 studies met the inclusion criteria. The studies included a total of 7,562 undergraduate dental students and were conducted in 18 countries. The review found that clinical students have good oral health attitudes and behavior compared with preclinical students, showing improvements in oral health attitude and behavior of dental students through the students’ educational progress. The improvement in oral health care has been shown to be linked to experience, especially for clinical students that have been in clinical settings.